Effect of GAD1 genotype status on auditory attention and acute nicotine administration in healthy volunteers. (29th November 2018) - Hadjis, Efthymios; Hyde, Molly; Choueiry, Joelle; Jaworska, Natalia; Nelson, Renee; de la Salle, Sara; Smith, Dylan; Aidelbaum, Rob; Knott, Verner
Abstract: Objective: The effects of GABA modulating drugs and nicotine, the prototypical nicotinic cholinergic agonist, on attention have been investigated using subcomponents of the P300 event‐related potentials (ERP), which index involuntary (P3a) and voluntary attention (P3b). However, investigations into how such pharmacologic effects interact with genetic features in the GABA system remain unclear. This study examined the moderating effects of a single nucleotide polymorphism (rs7557793) in the glutamic acid decarboxylase 67 (GAD1) gene, which is implicated in the conversion of glutamate to GABA, on P300‐indices of auditory attentional processing; the influence of nicotine administration was also assessed. Methods: The effects of GAD1 genotype (TT/CC/CT) were examined on the P3a/b in response to an auditory selective attention task in healthy, nonsmoking male volunteers ( N  = 126; 18–40 years). Participants responded to rare target stimuli (P3b‐eliciting) and ignored frequent nontarget stimuli as well as rare distractor stimuli (P3a‐eliciting). In a subsample ( N  = 59), P3a/b profiles to acute nicotine (vs. placebo) administration were examined as a function of GAD1 genotype. As a secondary aim, earlier sensory processes were assessed with N200 ERP subcomponents elicited by novel (N2a) and target (N2b) auditory stimuli. Results: GAD1 allelic variation moderated early sensory processes, enhancing N2a amplitudes in CT versus TT carriers. Further, TT homozygotes exhibited larger P3b amplitudes than CC homozygotes in the placebo versus nicotine condition. Regardless of genotype, nicotine versus placebo moderated the N200 ERP. Conclusion: These findings expand our knowledge regarding the attentional effects of GAD1 genetic variants in relation to nicotine.